Energy and inclination Analysis of the powered Swing-By maneuver in elliptical system - Ferreira, Alessandra F. S. [UNESP]; Moraes, Rodolpho [UNESP]; Prado, Antonio F. B. A.; Winter, Othon C. [UNESP]; AIAA (Amer Inst Aeronautics & Astronautics, 2020)
The three-dimensional and elliptical cases of the powered Swing-By maneuver are studied in the present paper. The system Sun-Mercury is adopted due to the high eccentricity of the system, but the study can be generalized for other systems with different sizes and masses. Maps of energy and inclination variations as a function of the control variables involved were made and analyzed. The results show the conditions favorable to the maximization and minimization of the energy and its respective conditions of orbit inclination. It is known that the Swing-By maneuver has the goal of fuel economy of a spacecraft in a space mission and that the powered case is recommended when the pure maneuver is not sufficient to meet the needs of the mission.